The reality of applying electronic supervision in public schools during the Corona pandemic period from the point of view of educational supervisors in the Northern Region of Jordan - Bakheet, Wafaa Ahmed (Journal of Educational and Psychological Sciences, 2021)
The study aimed to identify the reality of the application of electronic supervision in public schools during the period of the Corona pandemic from the point of view of educational supervisors in the Northern Region in Jordan, depending on the changing gender and years of experience supervisory and specialization. The research adopted the descriptive analytical approach. The researcher took from (the questionnaire) a main tool to take the opinions of the members of the sample of the study consisting of 50 supervisors.The results of the research showed the reality of the application of electronic supervision in public schools during the period of the Corona pandemic from the point of view of educational supervisors in the Northern Region in Jordan at the level of the whole tool obtained a total level (3.98 out of 5) with a rating (high). At the field level: the area (barriers to the use of electronic supervision) received the highest average (4.21) rating (very high). This is followed by the field (the importance of educational supervision) where the average (3.98), the field (the application of electronic supervision in supervisory work) where the level of response was (3.91), and finally the field (the concept of electronic supervision) where the level of response was (3.80) , all are rated (high).It also showed that there were no statistically significant differences at the level of (α≤0.05) the reality of the application of electronic supervision in public schools during the corona pandemic period from the point of view of educational supervisors in the Northern Region in Jordan due to the change of gender and years of experience supervisory and specialization in all dimensions and the overall degree where the level of significance of the values (T) was greater than (0.05).The researcher recommended the adoption of integrated education in Jordanian schools, even after the Corona pandemic, to meet exceptional circumstances. The educational supervisor should develop his supervisory practices to conform to the circumstances of the Corona pandemic and to the requirements of e- learning. Finally, the teacher is supported by educational media that he or she can rely on when designing his e- lessons.
Keywords: Electronic Supervision; Corona Pandemic; Educational Supervisor.